ANALYSIS OF THE PRINCIPLES OF ISLAMIC COMMUNICATION ETHICS (QAULAN) HUSAIN BASYAIBAN IN THE CONTENT OF “WOMEN'S ISSUES” ON THE TIKTOK PLATFORM - Angriany, Zulita Mega (Academic Solution Publisher, 2024)
In carrying out da'wah, ethics are something that cannot be missed and cannot be separated from the activity of conveying messages to providing solutions to the problems faced. Da'wah itself pays attention to the aspects of the principles or ethics of da'wah communication, namely the language structure conveyed, and the choice of words that will be correct. This is done so that the da'wah delivered is easily accepted and right on target. In carrying out the ethics of da'wah communication itself, it is clear that this ethics is based on the Qur'an and in the Qur'an itself there are 6 principles of da'wah communication, namely qaulan sadida, baligha, karima, layyina, maysura and ma'rufa. Da'wah in the technological era like today, certainly utilizes all the conveniences of the hands of intellectual humans. Including online communication media that offer many platforms called social media. One of them is Tiktok. Tiktok currently clearly does not seem old-fashioned and is being loved by all young people around the world. So that many young content creators have emerged with various types of fields of influence offered, including in the field of da'wah. Including Husain Basyaiban, a Tiktok influencer with 4.4M followers, offers preaching targeting (mad'u) young people, by bringing up hot topics and presenting them in a short, concise and precise form to suit the Tiktok features presented.